The dentition of Amygdalodon patagonicus (Dinosauria: Sauropoda) and the dental evolution in basal sauropods - Carballido, José Luis (2010)
Amygdalodon patagonicus is the oldest record of Sauropoda from South America and is known from several teeth and fragmentary postcranial remains. Here we describe in detail its dental morphology, characterized by the presence of broad spatulated teeth (with low SI values) and the absence of denticles in their crowns. The enamel bears a particular wrinkling pattern composed only of apicobasally-aligned pits, which are frequently joined to each other by a continuous sulcus. Some worn teeth have large wear-facets that extend over only one of the crown's edges. This unique combination of characters provides a proper diagnosis for Amygdalodon. Despite the fragmentary available material, Amygdalodon is here interpreted as a non-eusauropod sauropod based on the results of a phylogenetic analysis. The presence of derived dental characters in Amygdalodon, such as the presence of tooth-tooth occlusion, shows several features previously thought to diagnose Eusauropoda or Gravisauria appeared earlier during the early evolution of sauropods.